PENGARUH INDEKS REGIONAL TERHADAP JAKARTA ISLAMIC INDEX (JII) - Yoghi Citra Pratama (Faculty of Economic and Business, 2012)
The objectives of this study are to analyze the influence of IHSG, Dowjones, and Nikkei to JII. The data used in this study are monthly time series data from January 2006 – May 2012. Those data are JII, IHSG, Dowjones Index and Nikkei Index. Research method used in this study is Vector Error Correction Model (VECM). The cointegration test indicates that among research variables there is long term equilibrium and simultaneous relationship. The Empirical result of Impulse Response Function shown that the effect of IHSG, DowJones and Nikkei to JII are negative. The result on variance decomposition test had shown that the most effect of JII shock is influenced by JII itself. It can be conclude that Islamic Capital Market is more stable from the external shock rather than the conventional one.DOI: 10.15408/etk.v11i2.1888